2023
DOI: 10.3390/coatings13050902
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Solid Particle Erosion of Environmental and Thermal Barrier Coatings

Abstract: Solid particle erosion (SPE) is a common phenomenon observed in gas turbine engines. Particles entrained in the gas flow impact engine hardware, resulting in micro-scale damage that leads to deleterious effects such as material removal. For protective coatings, damage due to SPE is a key concern, since it can negatively affect the durability of the coating and subsequently the life of the underlying component. In this work, the high-temperature SPE behavior of two state-of-the-art environmental barrier coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Finally, it is observed that the chemical modifications to the M2Y EBC were not detrimental to the SPE resistance. In fact, the SPE resistance was slightly improved compared to the baseline Yb 2 Si 2 O 7 EBC 52 …”
Section: Current Statusmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, it is observed that the chemical modifications to the M2Y EBC were not detrimental to the SPE resistance. In fact, the SPE resistance was slightly improved compared to the baseline Yb 2 Si 2 O 7 EBC 52 …”
Section: Current Statusmentioning
confidence: 92%
“…It is expected that EBC/CMC components will replace at least some, if not all TBC/superalloy components in the hot section of gas turbines, so it is important to understand the relative erosion resistance between EBCs and TBCs. A comprehensive study was undertaken by the authors to compare the erosion rate of APS EBCs to APS and electron beam—physical vapor deposition (EB‐PVD) TBCs 52 . The study investigated a 100 wt.% Yb 2 Si 2 O 7 EBC (YbDS) and modified‐Yb 2 Si 2 O 7 EBC (M2Y) that consisted of balance Yb 2 Si 2 O 7 with additions of 1.39 wt.% mullite (3Al 2 O 3 ·2SiO 2 ) and 2.33 wt.% YAG (Y 3 Al 5 O 12 ).…”
Section: Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Particulate erosion is a common phenomenon observed in gas turbine engines. Composites with a ceramic matrix are the main candidates for protecting components of hot sections of gas turbine engines [16,17]. Calculation of the thickness of protective coatings is usually a complex multi-criteria optimization problem due to the contradictions that arise between the goals of the task: achieving high thermal insulation characteristics, ensuring long-term operation, manufacturability and low manufacturing cost [18][19][20].…”
Section: Introductionmentioning
confidence: 99%